Poetics of the Gustatories in the novel "Felix Austria" by S. Andrukhovich (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article analyzes the novel S. Andrukhovich «Felix Austria» in terms of gustative poetics, i.e. individual and specific taste; factors, features and properties of the products and dishes that indicate the olfactory features or taste responses; reflections of characters. The dishes in the novel «Felix Austria» have the following functions: healing, soothing and life-affirming. In addition, the novel presents cooking processes, with descriptions and explanations. The processes of cooking were the meaning of life for character Chef Steftsi, the girl was so in love with culinary magic, that her mood was directly proportional to whom she was cooking and what was the purpose of cooking.
Keywords: gustative; function; procedural descriptions; culinary magic